FORMULASI DAN EVALUASI SEDIAAN OBAT SUPPOSITORIA BASE OLEUM CACAO: LITERATURE REVIEW ARTICLE - Shania Nurhazidah; Fajar Prasetya; Dinar Utami; Dissa Andini; Gina Wijaya; Ali Alfaarizzy; Muhamad Atoriq; Nia Yuniarsih (Peneliti.net, 2023)
Suppositories are used for patients who have difficulty swallowing, have problems with the gastrointestinal tract, and for patients who are unconscious. Suppositories can be made rectally, ovules, and urethra. Evaluation of preparations is closely related to the effectiveness and quality of the preparations produced. Several tests were performed in evaluating suppository preparations. The data was obtained by electronic databases namely Google Scholar, PubMed, Media Neliti, Researchgate.Net, Sinta Kemendikbud and Science Direct. From the current literature study, 11 articles were produced that met the inclusion and exclusion criteria. The use of brown fat in suppositories is more efficient than other suppository bases because it has the fastest dissolution and permeation rates. Suppository preparations that use cocoa oleum as a base generally have very narrow melting and freezing points so that the preparation has ideal properties as a suppository. The most decisive factor in making suppositories is the choice of base, cocoa oleum is a base that has several characteristics that qualify as a suppository base, such as being able to melt at body temperature and being stable. Based on the results of the literature review articles that have currently been carried out, it can be seen that the addition of other ingredients to the suppository base mixture can modify the preparation and affect the level of stability of the resulting suppository.